Challenging beauty standards: A critical discourse analysis of the Vaseline advertisement on the VaselineID YouTube channel - Safira, Rahmalia Putri; Abrian, Risky (Direktorat Riset dan Pengabdian kepada Masyarakat UNY, 2025)
Every woman wants to be beautiful, with fair skin and a proportional body, as per societal standards. However, the existence of beauty standards makes women forget the true meaning of the word 'beautiful' itself. This research aims to reveal and describe the resistance made by young women in the Vaseline advertisement titled